Analisis Kinerja Biro Pemerintahan dan Kesejahteraan Rakyat Sekretariat Daerah Provinsi Bali Pasca Kebijakan Pengalihan Jabatan Struktural Menjadi Jabatan Fungsional - Ni Putu Shita Listya Dewi; Kadek Wiwin Dwi Wismayanti; Ni Wayan Supriliyani (CV. Lenggogeni Data Publishing, 2024)
This study analyzes the performance of the Work Team in the Bureau of Government and People's Welfare of the Bali Provincial Secretariat after the implementation of the policy of transferring structural positions to functional positions. An evaluative approach is used to evaluate the efficiency, effectiveness, fairness, and responsiveness of the Work Team in providing public services. The results showed that in some aspects, such as team formation, task coordination, and responsiveness to service users, the performance of the Work Team still needed improvement. Nonetheless, some supporting factors such as clear regulations on the duties and functions of the Work Team have helped in improving performance. Constraining factors include employees' unpreparedness to take competency tests or training and the lack of changes in the work system post-bureaucratic simplification. Recommendations include accelerating the employee competency test process and optimizing the functions of the Working Team to improve the quality of public services. Abstrak: Studi ini menganalisis kinerja Tim Kerja di Biro Pemerintahan dan Kesejahteraan Rakyat Setda Provinsi Bali setelah implementasi kebijakan pengalihan jabatan struktural menjadi jabatan fungsional. Pendekatan evaluatif digunakan untuk mengevaluasi efisiensi, efektivitas, keadilan, dan daya tanggap Tim Kerja dalam memberikan layanan publik. Hasil penelitian menunjukkan bahwa dalam beberapa aspek, seperti pembentukan tim, koordinasi tugas, dan responsif terhadap pengguna layanan, kinerja Tim Kerja masih membutuhkan penyempurnaan. Meskipun demikian, beberapa faktor pendukung seperti peraturan yang jelas tentang tugas dan fungsi Tim Kerja telah membantu dalam meningkatkan kinerja. Faktor penghambat termasuk ketidaksiapan pegawai dalam mengikuti uji kompetensi atau diklat dan kurangnya perubahan dalam sistem kerja pasca-penyederhanaan birokrasi. Rekomendasi termasuk mempercepat proses uji kompetensi pegawai dan optimalisasi fungsi Tim Kerja untuk meningkatkan kualitas pelayanan publik. Kata Kunci: Tim Kerja, kinerja, penyederhanaan birokrasi, layanan publik, efisiensi, efektivitas, keadilan, daya tanggap.